THE INFLUENCE OF PLANT EXCTRACTS ON ANTIBIOTIC TOLERANCE IN BACTERIAL BIOFILMS - Samoilova, Z.Yu.; Bezmaternykh, K.V.; Tyulenev, A.V.; Lepekhina, E.V.; Peters, M.A.; Ushakov, V.Yu.; Brysova, M.N. (Perm Federal Research Centre Journal, 2017)
The investigation results of the influence of plant extracts on biofilm formation by bacteria Escherichia coli BW25113 under treatment with antibiotics ciprofloxacin, cefotaxime and streptomycin and tolerance of bacterial cells in mature biofilms to these antibiotics are discussed.